Frequency of Transfusion Transmitted Infection Among Blood Donors at Specialized Tertiary Care Hospital in Bangladesh - Ara, Ferdous; Nasreen, Zubaida; Islam, Md Aminul; Yusuf, Md Abdullah; Hassan, Mohammad Syaeed; Sonia, Sheikh Farjana (Journal of National Institute of Neurosciences Bangladesh, 2015)
Background: Blood transfusion is associated with a number of complications. Transfusion transmitted infections (TTI) are one of the major health problem in Bangladesh. Objective: The objective of the present study was to assess the status of transfusion transmitted infections among the apparently healthy donors. Methods: This study we carried out among 585 blood donors in the transfusion medicine department from April 2013 to March 2014 at National Institute of Neurosciences (NINS) and Hospital in Dhaka, Bangladesh. All the samples were screened for hepatitis B surface antigen (HBsAg), hepatitis C virus (HCV), human immunodeficiency virus (HIV) 1 and 2, venereal disease research laboratory test (VDRL) and malaria to see the prevalence of TTI. Results: Prevalence of hepatitis B virus (HBV), HCV, and syphilis were 1.20, 0.68 and 0.34% respectively. No blood donor tested showed positivity for malarial parasite and HIV. Conclusion: Mandatory screening of donated blood and use of sensitive screening test should be done to reduce TTI in Bangladesh. J. Natl Inst. Neurosci Bangladesh 2015;1(1):12-14